Integrating a pedagogic course in a CPD programme for paediatricians at out-patient clinics. Issue 1 (1st January 2021) - Holmgren, Daniel; Vallo Hult, Helena; Wekell, Per
ABSTRACT: Equipping paediatricians for the challenges of the explosive development of knowledge and specialised health care calls for a well-planned continuing professional development (CPD) strategy which updates paediatric competencies and the pedagogic skills among paediatricians. The purpose of the study was to evaluate the effects of a pedagogic course, integrated into a CPD programme for paediatricians at out-patient clinics. The pedagogic course comprised three learning components, participation in a CPD programme, during two and a half years, a pedagogic learning module and a pedagogic assignment. The objectives of all the learning activities, including the pedagogic course, were developed according to adult learning theories. Evaluations were made using questionnaires. Seventeen paediatricians participated in the CPD programme; 13 of them completed the pedagogic learning module and six the full pedagogic course, including the pedagogic assignment – teaching at one's own clinic. Evaluation of the pedagogic assignment at the participants' own clinics by 64 co-workers revealed that the co-workers appreciated the training activities and would recommend them to a colleague. We conclude that it is possible to combine medical and pedagogic education in a CPD programme for paediatricians and that the participants were able to digest and apply the pedagogic principles used in the course.